Konformitas Teman Sebaya Terhadap Gaya Hidup Di Lingkungan Pertemanan - Rahmayanty, Dinny; Triana, Fira Febri; Ananta, Grestia; Andreani, Reva (Universitas Muhammadiyah Ponorogo, 2023)
Artikel ini mengeksplorasi konsep